Dermoscopic Pattern of Basal Cell Carcinoma in H- and Non-H-Zones - Joanna Pogorzelska-Dyrbuś; Natalia Salwowska; Beata Bergler-Czop (Mattioli1885, 2023)
Introduction: Basal cell carcinoma (BCC) localized in the H-zone, the region of fusion of embryonic masses, has been associated with a higher risk of deeper invasion and more frequent recurrence. Objectives: The aim of the study was to compare dermoscopic features of BCC in H and non-H zone that may most appropriately characterize those two locations. Methods: Dermoscopy images of histopathologically confirmed BCCs from 120 patients were retrospectively analyzed. Dermoscopy features of BCC in H- and non-H zone were described and a comparative study of the dermoscopic pattern of BCC between the two locations was performed. Results: Of 120 BCC cases included in this study, 41 (34.2%) were located in the H-zone. The most frequent histological type was nodular (51.3% in H- zone and 61.6 % in non-H-zone) followed by superficial (5.1% and 19.8 % in H and non-H-zone respectively). In dermoscopy, there was a higher prevalence of ulceration (73.2% versus 43.6%, P < 0.001) in H-zone and a lower prevalence of brown globules (26.8% versus 53.2%; P = 0.01), when compared with the non-H-zone. Conclusions: Our results show that dermoscopic features of BCC on the face fulfill a typical pattern regardless of the region, except for the prevalence of the ulceration which is significantly more frequent in H-zone and the brown globules present significantly more often in the non-H-zone It can be hypothesized that H-zone might predispose to more aggressive course of BCC complicated by ulceration and consequently deeper tissue destruction.